Conservation status and reintroduction of the Cocos Buff-banded Rail, Gallirallus philippensis andrewsi. (1st March 2016) - Woinarski, J. C. Z.; Macrae, I.; Flores, T.; Detto, T.; Reid, J.; Pink, C.; Flakus, S.; Misso, M.; Hamilton, N.; Palmer, R.; Morris, K.; Znidersic, L.; et al.
Abstract: An endemic subspecies of Buff-banded Rail ( Gallirallus philippensis ) is restricted to the Cocos (Keeling) Islands, a group of 27 islands, with total area of ~15 km 2, in the north-eastern Indian Ocean. Human settlement led to marked environmental degradation of the 26 islands in the southern atoll of the group. The Cocos Buff-banded Rail declined severely, with the last confirmed record from islands in the southern atoll in 1991. The subspecies has persisted, however, with a population of ~800 individuals, on a single island, Pulu Keeling, 24 km north of the southern atoll. A recovery plan for this endangered subspecies recommended reintroduction to a suitable island in the southern atoll. This paper provides a brief overview of the history and status of the subspecies, and describes an April 2013 reintroduction of 39 rails from Pulu Keeling to the 1-km 2 Horsburgh Island in the southern atoll. This program has had at least short-term success, with monitoring showing successful recruitment in the reintroduced population, and its increase to ~54 individuals by October 2014 and ~121 individuals by June 2015. Much of the world's loss of biodiversity has been from, and continues to occur on, islands: this project demonstrates that well-considered mitigation of threats and translocation programs can provide solutions to this challenge.